2019
DOI: 10.5334/pb.473
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Work Systems and Well-Being: Mediating Role of Work-to-Family Interface

Abstract: Regarding the effects of High-Performance Work Systems (HPWS), we can draw two conclusions. First, existing studies on the effects of HPWS on employees’ well-being at work are scarce. Second, few studies have considered the relationships between HPWS and work-to-family interface (i.e., work-to-family enrichment, WFE; and work-to-family conflict, WFC). Only one previous study conducted on a Portuguese sample (i.e., Carvalho & Chambel, 2016 ) has examined the relationships between these co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 82 publications
(156 reference statements)
2
11
0
Order By: Relevance
“…The poor psychological and/or physical health emerging from this situation of a loss of resources negatively affects individuals’ functioning at home ( Edwards and Rothbard, 2000 ), increasing women managers’ perceptions of WFC. Women managers perceiving WFC are more strained (e.g., Babic et al, 2015 , 2019 ) due to the loss of resources in the process of juggling work and family roles ( Hobfoll, 1989 ). In a such situation of WFC, they also are more likely to plan to leave their organization (e.g., Babic et al, 2015 ) and tend to reduce their level of engagement in their work (e.g., Babic et al, 2020 ) in order to preserve and protect their remaining resources ( Hobfoll, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The poor psychological and/or physical health emerging from this situation of a loss of resources negatively affects individuals’ functioning at home ( Edwards and Rothbard, 2000 ), increasing women managers’ perceptions of WFC. Women managers perceiving WFC are more strained (e.g., Babic et al, 2015 , 2019 ) due to the loss of resources in the process of juggling work and family roles ( Hobfoll, 1989 ). In a such situation of WFC, they also are more likely to plan to leave their organization (e.g., Babic et al, 2015 ) and tend to reduce their level of engagement in their work (e.g., Babic et al, 2020 ) in order to preserve and protect their remaining resources ( Hobfoll, 1989 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in their study on firefighters in Taiwan, Wong et al (2014) found a positive relationship between WFC and job strain. In studies of employees of a Belgian hospital ( Babic et al, 2015 ) and of employees of a Belgian company ( Babic et al, 2019 ), WFC was also found to be positively related to job strain.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Researchers have found that individual outcomes mediate a dominant part of the impact of HPWS on organizational performance (Zhang and Morris, 2014). Positive individual outcomes of HPWS include work engagement (Babic et al. , 2019), affective commitment (Zhang et al.…”
Section: Theoretical Background and Hypothesismentioning
confidence: 99%
“…On the other hand, this study provides a lens to understand the equivocal findings on the relationship between HPWS and work-to-family interface. Reviewing the literature, there is research reporting that HPWS is good for work-to-family experience (e.g., Babic, Stinglhamber, & Hansez, 2019;Wattoo, Zhao, & Xi, 2020), but there is also research indicating that HPWS is bad for work-to-family experience (e.g., Shih, Chiang, & Hsu, 2010;White et al, 2003). Considering two forms of work-to-family interface (i.e., WFC and WFE) and two underlying mechanisms (i.e., the motivational process and the strain process), our research indicates that SHPWS both enhances WFE through customer orientation and induces WFC through service workload.…”
Section: Theoretical Implicationsmentioning
confidence: 99%